The Choice Of Green And Sustainable Kitchen Component In Condominium Units In Penang - Oo, Jia Huey (2013)
Kitchens are the heart of activity in any home. Today, a modern urban lifestyle, changing habits, communication technology etc. have been transforming the face of present day kitchens design in Malaysia. The topic of this master thesis is the investigation of kitchen component that evolved towards a multifunctional, green and sustainable nature. The objective of this research are to identify the issues that determine the existing kitchen design in Penang condominium units, to find out the needs and the choice of the kitchen component related to the factors in existing kitchen design in Penang condominium units and to identify the green and sustainable kitchen component choices. The scope of the study was focuses on kitchen interior design in condominium units. The purposes of the study are to study the issues faces of the existing kitchen design and to understand the usage of the kitchen component applying to kitchen design. The findings of the research will assist the kitchen industry to move towards green and sustainable theme in the future. The methodology adopted in this research was using the sequential explanatory mixed methods. The qualitative data was obtained by using questionnaire survey and the qualitative data through observation and face-to-face interview. Not enough storage is the main issue face for the existing kitchen at the moment for Penang condominium units. The survey found that the choice of the kitchen design for all residents irrespective of race prefer modern style kitchen and majority of them agree that green and sustainable kitchen would be preferable for future renovations. The four kitchen zones are important for food preparation, cooking, cleaning, and storing in every kitchen design and it could be achieved through a proper understanding of kitchen layout and its design. The research will add to new knowledge and trigger further research in kitchen related design.